The Existence of The Principle of Balance and The Principle of Freedom of Contract in Fiduciary Agreements After The Decision of The Constitutional Court - Hariyana, Trinas Dewi (UNISKA LAW REVIEW, 2025)
The fiduciary gives the creditor the right to parate execution of the debtor's fiduciary object without waiting for a court decision as stipulated in Article 29 paragraphs (1) and (2) of the Fiduciary Law. The Constitutional Court Decision Number 18/PUU-XVII/2019 in its decision states that there are 2 conditions that must be met by creditors to carry out parate executions, namely the debtor must admit that he is in default, and the debtor must voluntarily surrender the object that is a fiduciary object. Then how about the existence of the principle of freedom of contract and the principle of balance in a fiduciary agreement after the Constitutional Court's decision Number 18/PUU-XVII/2019. This research uses a normative juridical method with a statute approach and conceptual approach. The decision of the constitutional court in limited the rights of creditors. The clause on default and parate execution is certainly considered Contrary to the decision of the constitutional court and results in the position of the creditor being unbalanced because the debtor becomes the dominant position because the creditor can only execute parate execution if it fulfills 2 conditions.